Microfluidization initiated cross-linking of gliadin particles for structured algal oil emulsions. (December 2017) - Liu, Xiao; Liu, Yu-Yang; Guo, Jian; Yin, Shou-Wei; Yang, Xiao-Quan
Abstract: The interfacial covalent cross-linking of emulsions can greatly enhance their tolerance to environmental stresses, and also contribute to formation of a new class of food products (e.g., oil gel, oil powder, and capsules). Algal oil is rich in ω-3 polyunsaturated fatty acids, while heat treatment makes it particularly susceptible to oxidation. In this study, microfluidization initiated interfacial covalent cross-linking of gliadin particles to stabilize emulsion as a novel technology to facilely construct structured algal oil product without any thermal or chemical treatment. The coarse emulsions with high algal oil volume fraction ( φ oil= 50%) stabilized by acidic gliadin particles were firstly homogenized using IKA homogenizer, and then emulsions were immediately subjected to mild alkaline pH-shifting processes. Finally, microfluidization initiated cross-linking of gliadin via intermolecular disulfide bonds to prepare stable structured emulsions. The droplet size distribution, FTIR, and SDS-PAGE of emulsions clearly verified that cross-linking was initiated by hydrophobic interaction under mild alkaline conditions, and interfacial disulfide cross-linking of gliadins was triggered by microfluidization. The viscoelastic and mechanical properties of emulsions showed homogenization pressure-dependent behavior. In addition, with increasing homogenization pressure, the increased oxidative stability with reduced lipid hydroperoxides and volatile hexanal of emulsions was also observed. Facile construction of cross-linking by microfluidization may provide a novel technology platform for gliadin based delivery system or edible oil structuring with functional characteristics. Graphical abstract: Highlights: Microfluidization initiated interfacial disulfide cross-linking of gliadin particles to stabilize emulsion as a novel technology to facilely construct structured algal oil product without any thermal or chemical treatment. The viscoelastic and mechanical properties of structured emulsions showed homogenization pressure-dependent behavior. Higher homogenization pressure could increase oxidative stability of emulsions.